The associations of diet quality and cardiometabolic indicators in children and the mediation role of cardiorespiratory fitness - Zhang, Ping-Ping; Lin, Gao-Feng; Gu, Jia-Ying; Wang, Bi-Lian; Zhang, Jie; Zhou, Ye; Xu, Miao; Wang, Hui; Li, Li (Frontiers in Nutrition, 2025)
BackgroundCardiometabolic health in children has become a growing global concern due to its long-term association with chronic diseases such as cardiovascular disease and type 2 diabetes. Diet quality plays a critical role in determining cardiometabolic health. This study explored the association between diet quality and cardiometabolic health indicators in Chinese children aged 8–10 years and assessed the mediating role of cardiorespiratory fitness (CRF).MethodsA total of 1,389 third-grade students from Ningbo, China were included. Diet quality was assessed using a validated questionnaire to calculate a Global Dietary Recommendations (GDR) score, with higher scores indicating healthier dietary patterns. Anthropometric data and fasting blood samples were collected to evaluate metabolic markers. A cardiometabolic risk (CMR) score was calculated based on age- and sex-adjusted Z-scores for waist circumference, systolic blood pressure, triglycerides, total cholesterol to high-density lipoprotein cholesterol ratio, and homeostasis model assessment for insulin resistance (HOMA-IR). CRF was measured using the 20-meter shuttle run test. Generalized linear mixed models were used to examine associations, and mediation analysis was conducted to assess the mediating effect of CRF.ResultsAfter adjusting for age, sex, and physical activity, higher GDR scores were significantly associated with lower fasting insulin (β = −0.013; p = 0.023), lower HOMA-IR (β = −0.014; p = 0.019), and reduced CMR score (β = −0.074; p = 0.030). Stratified and interaction analyses revealed stronger associations in girls than in boys. Mediation analysis showed that CRF accounted for 26.1% of the association between GDR score and fasting insulin, 25.3% for HOMA-IR, and 32.9% for CMR score (all p < 0.05).ConclusionIn Chinese children, better diet quality is associated with more favorable cardiometabolic profiles. CRF showed a statistically significant mediating role in the cross-sectional association, highlighting the potential importance of both healthy eating and physical fitness in promoting cardiometabolic health in youth.